Cost analysis of antibiotic therapy versus appendectomy for treatment of uncomplicated acute appendicitis: 5-year results of the APPAC randomized clinical trial - Jussi Haijanen; Suvi Sippola; Risto Tuominen; Juha Grönroos; Hannu Paajanen; Tero Rautio; Pia Nordström; Markku Aarnio; Tuomo Rantanen; Saija Hurme; Paulina Salminen (Public Library of Science, 2022)
Background
The efficacy and safety of antibiotic treatment for uncomplicated acute appendicitis has
been established at long-term follow-up with the majority of recurrences shown to occur
within the first year. Overall costs of antibiotics are significantly lower compared with appendectomy
at short-term follow-up, but long-term durability of these cost savings is unclear.
The study objective was to compare the long-term overall costs of antibiotic therapy versus
appendectomy in the treatment of uncomplicated acute appendicitis in the APPAC (APPendicitis
ACuta) trial at 5 years.
Methods and findings
This multicentre, non-inferiority randomized clinical trial randomly assigned 530 adult
patients with CT-confirmed uncomplicated acute appendicitis to appendectomy or antibiotic
treatment at six Finnish hospitals. All major costs during the 5-year follow-up were recorded,
whether generated by the initial visit and subsequent treatment or possible recurrent appendicitis.
Between November 2009 and June 2012, 273 patients were randomized to appendectomy
and 257 to antibiotics. The overall costs of appendectomy were 1.4 times higher
(p<0.001) (€5716; 95% CI: €5510 to €5925) compared with antibiotic therapy (€4171; 95%
CI: €3879 to €4463) resulting in cost savings of €1545 per patient (95% CI: €1193 to €1899;
p<0.001) in the antibiotic group. At 5 years, the majority (61%, n = 156) of antibiotic group
patients did not undergo appendectomy.
Conclusions
At 5-year follow-up antibiotic treatment resulted in significantly lower overall costs compared
with appendectomy. As the majority of appendicitis recurrences occur within the first year
after the initial antibiotic treatment, these results suggest that treating uncomplicated acute
appendicitis with antibiotics instead of appendectomy results in lower overall costs even at
longer-term follow-up.